The invasion of Sennacherib in the book of Kings : a source-critical and rhetorical study of 2 Kings 18-19 - Evans, Paul S. (Vetus Testamentum, Supplements, 2009)
The invasion of Sennacherib in 701 BCE is a classic issue for both biblical scholars and historians alike. Extant Assyrian, Biblical and even Greek texts all refer to Sennacherib and many different theories have been put forward in attempts to understand the relationship between these various accounts. Despite the rise of new literary-rhetorical criticism in biblical studies, studies tackling the problem of Sennacherib's invasion have been dominated by historical-critical work on the issue and have virtually ignored rhetorical methodology. Against this trend, this book employs both traditional historical-critical methods and newer rhetorical methods in an effort to utilize the biblical texts in a historical reconstruction of this famous Assyrian assault on ancient Judah.